Nutritional and microbiological quality assessment of commercial yogurt sold in different districts of Bangladesh: a food safety issue (Asian-Australasian Journal of Food Safety and Security, 2020)
The aim of this study was to investigate the nutritional and microbial quality of yoghurt from different districts of Bangladesh. Protein content was higher (4.56g/kg) in SB2 (sample Bogura-2), fat content was also higher (5.67g/kg) in SB3 (sample Bogura-3). The acidity found ranged from 0.77% to 0.98%, pH obtained ranged between 3.6 to 4.98 and total solid retained between 23.08 to 26.95 for all samples. Highest Total Viable count (TVC) value was found in SB2 (68.9×104±0.23 CFU/ml) and lowest value was observed in SJ2 (23.01×104±0.43 CFU/ml). No mold and yeast were found in the collected samples during study period that indicates all are follow hygiene procedure but all of the yogurt samples were contaminated with fewer amount (5.6±0.66 to 12.56±0.44 CFU/ml) of coliform. The mean value of acceptability score of yogurt sample was higher (99.2) in SB2 (sample Bogura-2) during the study period. Organoleptically, the overall quality of all yogurt samples was good. Considering the pH, acidity, total solids, protein, fat, carbohydrate and ash values for all yogurt samples collected from Bogura had better quality as compared to other samples. From the present study, it was found that all of the samples collected from Bogura district were much better quality compared to other samples in terms of nutritional, biochemical and microbial aspect. All of the samples were found in contaminated with lower amount of coliform so necessary actions should be taken in every step of processing, maturing and marketing to overcome this problem.Asian Australas. J. Food Saf. Secur. 2020, 4 (2), 66-72